Um turista bem moderno: a expressão amazônica de Mário de Andrade na literatura e na fotografia - Langfeldt, Marcia Caetano (Bergen Language and Linguistics Studies, 2019)
Mário de Andrade (1893-1945) was a Brazilian poet, novelist, literary critic, ethnographer, musicologist, art critic as well as a competent photographer and a dedicated researcher of Brazilian folklore. In 1927, he travelled to the Amazon together with three female friends. During this trip, he published a series of articles in a national newspaper, wrote two diaries, collected notes and finished his most important book, Macunaima, considered the reference of Brazilian Modernism. In addition to that, he took more than 500 photos of the journey, most of them in a very modern perspective. This paper investigates to what extent these various representations of the Amazon contribute to Mario de Andrade’s aesthetic project, as a Brazilian intellectual from the first quarter of the twentieth century,